Innovation As Success Factor For Smes' Business Performance At Northern Region Of Malaysia - Toh, Seong Thye (2014)
The objective of this research is to examine the relationship between each innovation (product innovation, process innovation, marketing innovation, and organization innovation) and business performance (financial and non-financial performance) of Northern Malaysia's SMEs. Additionally, government support as external environment had also been explored as moderating factor in the research. The survey was conducted among 120 SMEs within Perlis, Kedah, Penang and Perak states. This research had built a framework based upon the resource based view theory. Data collected was analyzed using SPSS and SmartPLS statistical tool. The results shows product innovation, process innovation and organization innovation were significantly affect financial and non-financial performance. However, marketing innovation was not significantly affect financial and non-financial performance. Government support as external environment was not a significant moderator. In summary, SME is advised to have innovation as corporate strategy in order to raise business performance, thereafter continuous to grow as bigger firm and stand invulnerable in global market.